2017
DOI: 10.1108/wwop-08-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering with older people in a care home

Abstract: Purpose The purpose of this paper is to investigate the influence that volunteering before medical school with older people in a care home has on the perceptions of older people. Design/methodology/approach Eight medical students answered an anonymous questionnaire relating to their experiences of volunteering in a care home before medical school. This was combined with an analysis of the relevant literature. Findings All the students had initially volunteered to enhance their CV for medical school. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Details of individual studies are reported in Table 1. Fourteen quantitative or mixed methods studies evaluated the impact of volunteering (Baker et al., 2017; Caspar et al., 2019; Clarkson et al., 2007; Di Bona et al., 2019; Lee et al., 2007; Lokon et al., 2017; Low et al., 2015; McNair & Moore, 2010; Sauer et al., 2016; Seitz et al., 2016; Skropeta et al., 2014; van Zon et al., 2016; Westerhof et al., 2018; Xaverius & Mathews, 2004), and 22 reported questionnaire or qualitative data (Biggs & Knox, 2014; Bradley et al., 2000; Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Hill, 2016; Hunter et al., 2018; Jain et al., 2020; Kawamura et al., 2009; Keith, 2001; Keith & Schafer, 2002; Landau et al., 2013; Lokon et al., 2012; Ostwald et al., 2003; Persson, 2004; Santini et al., 2018; Schwalbach & Kiernan, 2002; Somers, 2018; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012, 2014). Overall the quality of studies is poor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of individual studies are reported in Table 1. Fourteen quantitative or mixed methods studies evaluated the impact of volunteering (Baker et al., 2017; Caspar et al., 2019; Clarkson et al., 2007; Di Bona et al., 2019; Lee et al., 2007; Lokon et al., 2017; Low et al., 2015; McNair & Moore, 2010; Sauer et al., 2016; Seitz et al., 2016; Skropeta et al., 2014; van Zon et al., 2016; Westerhof et al., 2018; Xaverius & Mathews, 2004), and 22 reported questionnaire or qualitative data (Biggs & Knox, 2014; Bradley et al., 2000; Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Hill, 2016; Hunter et al., 2018; Jain et al., 2020; Kawamura et al., 2009; Keith, 2001; Keith & Schafer, 2002; Landau et al., 2013; Lokon et al., 2012; Ostwald et al., 2003; Persson, 2004; Santini et al., 2018; Schwalbach & Kiernan, 2002; Somers, 2018; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012, 2014). Overall the quality of studies is poor.…”
Section: Resultsmentioning
confidence: 99%
“…Nine papers discussed volunteer motivations for their involvement with care homes and care home residents (Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Keith, 2003; Lokon et al., 2012; Ostwald et al., 2003; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012). These included a desire to help others or “give something back” (Damianakis & Wagner, 2007; Gundersen & Johannessen, 2018; Keith, 2003; Ostwald et al., 2003; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012); providing the volunteer with a sense of purpose (Damianakis & Wagner, 2007; Filinson, 2003; Van der Ploeg et al., 2012); utilising personal and professional experiences (Damianakis & Wagner, 2007; Keith, 2003; Tanner & Brett, 2014; Van der Ploeg et al., 2012) and using volunteer opportunities to enhance career prospects (Lokon et al., 2012; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Tinker et al (2017) investigated the influence that volunteering with older people in a care home has on the medical students’ perceptions of older people. They reported achieving a better understanding of older people and gaining transferable skills related to communicating with them, especially those with cognitive impairment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%